2010
DOI: 10.1002/ijc.25622
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of strain background and a high omega‐6 fat diet induces earlier onset of pancreatic neoplasia in EL‐Kras transgenic mice

Abstract: Diets containing omega-6 (x-6) fat have been associated with increased tumor development in carcinogen-induced pancreatic cancer models. However, the effects of x-6 fatty acids and background strain on the development of genetically-induced pancreatic neoplasia is unknown. We assessed the effects of a diet rich in x-6 fat on the development of pancreatic neoplasia in elastase (EL)-Kras G12D (EL-Kras) mice in two different backgrounds. EL-Kras FVB mice were crossed to C57BL/6 (B6) mice to produce EL-Kras FVB6 F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 32 publications
1
25
0
Order By: Relevance
“…In flaxseed and in fish oil, n-3 polyunsaturated FAs (n3PUFAs) also contribute as principal FAs [1]. Previous studies have shown that increased FAs regulate pancreatic cancer [2][3][4][5][6][7][8]. For instance, diets rich in SFAs and n6PUFAs accelerate the process of pancreatic carcinogenesis in the animal, whereas HFDs made of fish oil and thus rich in n3PUFAs sometimes inhibit the carcinogenetic process [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…In flaxseed and in fish oil, n-3 polyunsaturated FAs (n3PUFAs) also contribute as principal FAs [1]. Previous studies have shown that increased FAs regulate pancreatic cancer [2][3][4][5][6][7][8]. For instance, diets rich in SFAs and n6PUFAs accelerate the process of pancreatic carcinogenesis in the animal, whereas HFDs made of fish oil and thus rich in n3PUFAs sometimes inhibit the carcinogenetic process [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…We have previously demonstrated that EL-Kras mice fed a diet rich in omega-6 fatty acids have increased lesion numbers and increased mast cell infiltration [16]. Since LTB4 is a potent chemotactic factor for mast cells [12], we extended these findings into human cells by determining the effect of omega-6 fatty acids on LTB4 production in vitro .…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we reported that EL-Kras mice fed diets rich in omega-6 fatty acids demonstrated increased pancreatic mast cell infiltration [16]. Significantly, increased infiltration of mast cells into the tumor microenvironment correlates with a poor prognosis [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…140 Obesity and a high fat diet are directly linked with the incidence of human pancreatic cancer. 141143 …”
Section: Regulation Of Metabolic Activity By Mirnasmentioning
confidence: 99%